Changes in Communication Media in Family Communication Patterns in The Digital Era (Proceeding of Dakwah Saizu International Conference, 2023)
Advances in information and communication technology greatly affect changes in communication patterns in family life. Technological advances can certainly change the way family members communicate. Not only the way of communicating, but the communication media used today is also changing. Changes in communication media make the current family communication pattern less harmonious. As we know, communication is very important in life, especially in the family. This research uses a literature study research method, namely about changes in communication media in family communication patterns in the digital era. The purpose of this study is to determine the changes in communication media in family communication patterns in the digital era and how the family communication process in the digital era. The method used is a literature study with information collection techniques from various written sources. The sources used are , books, and journals that are relevant to with changes in communication media in family communication patterns in the digital era. The theory used is Technological Determinism. Communication is a very important thing, but if communication is less effective, it will certainly be a problem, especially in the family. The existence of communication in the family, of course, the family will be harmonious. Changes in communication media in families in the digital era are certainly a reason for researchers to examine this.